Crosslinked PVDF membranes for aqueous and extreme pH nanofiltration - Van Goethem, Cédric; Mertens, Matthias; Vankelecom, Ivo F.J. (Journal of membrane science, 2019)
Loose poly(vinylidene difluoride) nanofiltration membranes were crosslinked using a one-pot reaction with para-xylenediamine in alkaline conditions. The crosslinking reaction was characterized using ATR-FTIR and EDX-based elemental analysis as function of reaction time. Upon crosslinking, the retention of the membranes improved dramatically for rose Bengal (RB) (from 90% to 100%) and MO (from 49% to 91%) without significant loss of permeability. The physico-chemical changes of the membrane during the crosslinking reaction were further characterized through XRD, TGA, DSC and DMA. Crosslinking resulted in a strong decrease in crystallinity of the semi-crystalline PVDF and tensile strength and thermal stability. The 24 h crosslinked PVDF membranes were tested for NF application in extreme pH conditions. The membranes were found to be suitable in both extreme acidic and alkaline conditions (5 M HCl or NaOH). The RB retention was not affected at all by the extreme conditions. Although a small decrease in permeance was observed for the acid treated membrane, the permeance of the alkaline treated membrane was not affected. This proves that crosslinking is a suitable strategy to improve the stability of PVDF, especially in alkaline conditions where pristine PVDF is not applicable at all, and furthermore is a tool to decrease the MWCO. •PVDF NF membranes were crosslinked using one-pot diamine reaction.•Crosslinking resulted in lower MWCO.•Crosslinked membranes showed promising performance in extreme pH nanofiltration.•Crosslinking was characterized through SEM-EDX, XRD, TGA, DSC and DMA.